Advanced age promotes colonic dysfunction and gut‐derived lung infection after stroke. Issue 5 (14th June 2019) - Wen, Shu Wen; Shim, Raymond; Ho, Luke; Wanrooy, Brooke J.; Srikhanta, Yogitha N.; Prame Kumar, Kathryn; Nicholls, Alyce J.; Shen, SJ.; Sepehrizadeh, Tara; de Veer, Michael; Srikanth, Velandai K.; Ma, Henry; et al.
Abstract: Bacterial infection a leading cause of death among patients with stroke, with elderly patients often presenting with more debilitating outcomes. The findings from our retrospective study, supported by previous clinical reports, showed that increasing age is an early predictor for developing fatal infectious complications after stroke. However, exactly how and why older individuals are more susceptible to infection after stroke remains unclear. Using a mouse model of transient ischaemic stroke, we demonstrate that older mice (>12 months) present with greater spontaneous bacterial lung infections compared to their younger counterparts (7–10 weeks) after stroke. Importantly, we provide evidence that older poststroke mice exhibited elevated intestinal inflammation and disruption in gut barriers critical in maintaining colonic integrity following stroke, including reduced expression of mucin and tight junction proteins. In addition, our data support the notion that the localized pro‐inflammatory microenvironment driven by increased tumour necrosis factor‐α production in the colon of older mice facilitates the translocation and dissemination of orally inoculated bacteria to the lung following stroke onset. Therefore, findings of this study demonstrate that exacerbated dysfunction of the intestinal barrier in advanced age promotes translocation of gut‐derived bacteria and contributes to the increased risk to poststroke bacterial infection. Abstract : Advanced age increases the risk of poststroke infection. Our results suggest that advanced age in older animals promotes the breakdown of colonic barriers after stroke via a tumour necrosis factor‐α‐mediated pathway, allowing for the translocation of commensal bacteria to distant organs such as the lung. For the graphical abstract, stock images sourced from Servier Medical Art; Creative Commons.